LCMV‐specific CD4 T cell dependent polyclonal B‐cell activation upon persistent viral infection is short lived and extrafollicular. Issue 3 (27th November 2019) - Greczmiel, Ute; Kräutler, Nike J.; Borsa, Mariana; Pedrioli, Alessandro; Bartsch, Ilka; Richter, Kirsten; Agnellini, Paola; Bedenikovic, Gregor; Oxenius, Annette
Abstract: Persistent virus infections with non‐ or poorly cytopathic viruses are commonly associated with B cell dysregulations. These include the induction of hypergammaglobulinemia and the emergence of virus‐unspecific antibodies. These seemingly unspecific antibody responses interfere with the virus‐specific humoral immunity and contribute to delayed virus control. Whether these virus‐unspecific antibodies are induced in the B cell follicle or at extrafollicular sites and whether one specific CD4 T cell subset is involved in the polyclonal B cell activation is unclear. Here we studied virus‐unrelated IgG antibody responses against self or foreign antigens in the context of persistent lymphocytic choriomeningitis virus (LCMV) infection. We found that the LCMV‐unspecific antibody response is short‐lived and induced predominantly at extrafollicular sites and depends on the presence of LCMV‐specific CD4 T cells. Our data support a scenario in which activated, virus‐specific CD4 T cells provide help to non‐specific B cells at extrafollicular sites, supporting the production of virus unspecific IgG antibodies during persistent viral infection. Abstract : Chronic LCMV infection induces an LCMV‐unspecific antibody (IgG) response, which is short‐lived, and is induced predominantly at extrafollicular sites. This unspecific IgG response depends on the presence of LCMV‐specific CD4 T cells.